1990
DOI: 10.1097/00006842-199001000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular response patterns and speech: a study of air traffic controllers.

Abstract: The present study examined the relationship between cardiovascular (CVS) response and speech among air traffic controllers (ATCs). During two one-hour work sessions continuous EKG, ear pulse, and audio recordings were obtained individually from 24 male ATCs. In one session the controller actively controlled aircraft, while in the other he worked in a support/coordinator position. Session time in both conditions was partitioned on the basis of audio recordings into four mutually exclusive activities: Radio/Phon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Another approach to the study of the cardiovascular correlates of naturally occurring interpersonal communication involves employing a particular workforce as participants~Henderson, Bakal, & Dunn;Jamner, Shapiro, Goldstein, & Hug, 1991;Sausen, Lovallo, Pincomb, & Wilson, 1992!. Work site studies permit the evaluation of the cardiovascular correlates of real-life stressors under relatively consistent conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach to the study of the cardiovascular correlates of naturally occurring interpersonal communication involves employing a particular workforce as participants~Henderson, Bakal, & Dunn;Jamner, Shapiro, Goldstein, & Hug, 1991;Sausen, Lovallo, Pincomb, & Wilson, 1992!. Work site studies permit the evaluation of the cardiovascular correlates of real-life stressors under relatively consistent conditions.…”
mentioning
confidence: 99%
“…investigation of air traffic controllers, studies of employees have not explicitly examined episodes of interpersonal interaction. Henderson et al~1990! reported that work-related communication was generally associated with sympathetic activation but of a lower intensity than expected, possibly because the workload at the time of the study was below normal.…”
mentioning
confidence: 99%
“…. However, several studies (e.g.,Henderson, Bakal, & Dunn, 1990;Kelsey, 1991; Linden, 1987) have demonstrated that speech rate has minimal effects on measures of autonomic reactivity to stress, so it is unlikely that the increased speech rate can entirely explain the relative magnitude of the…”
mentioning
confidence: 99%
“…. However, several studies (e.g.,Henderson, Bakal, & Dunn, 1990;Kelsey, 1991; Linden, 1987) have demonstrated that speech rate has minimal effects on measures of autonomic reactivity to stress, so it is unlikely that the increased speech rate can entirely explain the relative magnitude of the This document is copyrighted by the American Psychological Association or one of its allied publishers.This article is intended solely for the personal use of the individual user and is not to be disseminated broadly.…”
mentioning
confidence: 99%
“…Several methods are available to analyze mental activities. Subjective measurements such as self-reports [1], [2], performance measurements [3], body posture/movements [4], objective measurements such as physiological indicators [5] are typical examples of methods often applied to analyze the mental activities. However, some of those approaches suffer partially from limitations in predictive power and general applicability [6].…”
Section: Choice Of the Investigation Methodsmentioning
confidence: 99%